FAKTOR IKLIM DAN SIFAT FISIK KIMIA TANAH YANG BERKORELASI TERHADAP PRODUKSI PADI SAWAH DAN JAGUNG DI KABUPATEN KULON PROGO - , Apik Nusantari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Influence of the current global climate has uncertain variations and difficult predict. One of the effects of climatic variations on agriculture is decreasing the amount of production. Rice and corn are excellent commodities in Indonesia as well as a staple food of Indonesian society. Declining production can be affected by environmental factors, namely the soil properties and climate. Physical and chemical properties of the soil that is closely related to the availability of plant nutrients may be a limiting factor of rice and corn production if availability does not meet the needs of the plant. Rainfall and extreme temperatures may causing crop failures that decrease the amount of production. This study aims to determine the climatic factors and physical properties of any chemical that is highly correlated to the production of rice and corn in Kulon Progo Regency. This research was conducted at six Districts, namely: Girimulyo, Panjatan, Sentolo, Galur, Kalibawang and Temon. Climatic factors observed namely rainfall and temperature, whereas the observed soil factors were the physical and chemical properties of the soil. Data analysis used correlation and regression analysis to determine the relationship of each factor on the production of rice and corn. Kulonprogro is an area that excel in achieving food selfsufficiency. K (Potassium) is an element that affects the availability of rice production, while P (Phosphorus) is an element that affects the availability of maize production in Kulon Progo Regency. Rainfall is a factor that is highly correlated to the production of rice and is very closely related to the availability of K nutrients in the soil. The number of high rainfall in the area during the rainy season Kulon Progo caused K nutrient leaching and reduced its availability to plants.